Prediction of Scoring Skills from the Persistence of Basketball in Terms of Cognitive-kinetic Abilities of School Children Aged 11 Years - Zahraa Ihsan Abd Aoun (Journal of Global Pharma Technology, 2016)
The introduction and problem of research on childhood, which is one of the most important stages in human life, has been manifested by its great impact on its future life because it is the basis on which the rest of its life is built and through which the basic concepts are formed, as well as the proper planning of the educational and educational process because it Comprehensive studies of all aspects of the child involved (mental, motor, physical, emotional), where the growth of those aspects intersect, each one is affected by the other. Cognitive-kinetic abilities are the ones that the specialists sought to study and reveal their levels and the objective of the study was to:To recognize the level of cognitive-kinetic abilities and the skill of correction from the constant basketball of schoolchildren in the center of Kerbala Governorate aged 11 years.To identify the contribution ratios of cognitive-kinetic skills for the correction of the school attendance of schoolchildren in the center of Kerbala Governorate.Forecasting of the skill of the correction of a basketball constant in the meaning of cognitive-kinetic abilities of schoolchildren in the center of Kerbala Governorate.The researchers used the descriptive method of surveying and mutual studies (correlation and comparison), the researcher identified her research community for elementary school pupils in the center of Kerbala Governorate. The selection of her research sample was made with a simple random sampling method and (260 pupils), used Statistical pouch Researcher (SPSS).One of the most important conclusions:There are significant percentages of some cognitive - motor abilities in the skill of correction of the stability of basketball in primary school students.The development of predictive equations for the skill of correction of the stability of the basketball in terms of cognitive abilities - kinetic to elementary school pupil's model.Keywords: Prediction, Scoring skills, Cognitive-kinetic abilities and schoolchildren.